Pelatihan mikroskopis dan entomologi pada tenaga laboratorium dan entomologis lokal di Kecamatan Kokap untuk mendukung eliminasi malaria di Kabupaten Kulon Progo, DIY - Elsa Herdiana Murhandarwati; Rizqiani Amalia Kusumasari; Purwono Purwono; Kuswati Kuswati; Sulistyawati Sulistyawati; Sitti Rahmah Umniyati; Mahardika Agus Wijayanti; Tri Baskoro Tunggul Satoto (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Malaria is a serious public health problem in Indonesia. This disease is one of several indicators that have been targeted by the Millennium Development Goals (MDGs) 2015 to become Sustainable Development Goals (SDGs). In malaria-endemic areas such as in Kokap, Kulon Progo, Yogyakarta, reported malaria cases declined in 2000 with no case, but increased in 2011 following by some outbreaks in 2012. Future outbreaks could be avoided when health personnel including Primary Health Care (PHC) microscopists and entomologist surveyors were equipped with adequate trainings related to malaria. This training also be used for refreshment for existing personnel to support elimination at the Kokap I, Kokap II, and several nearby PHCs. In October 2013, the Department of Parasitology, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada carried out microscopic training and basic entomology related to malaria in the working area of PHC in Kokap. Training methods were giving material and direct activities in the field. The training provided basic entomology training, malaria microscopic training and malaria vector mapping using a Global Positioning System (GPS). The training facilitated PHC personnel to do correct identification of Plasmodium species, identification of old and new vector breeding sites, and found out how to map vector distribution and malaria cases in their area. The results showed that there was an increase in knowledge from PHC personnel who participated in the pre-test and post-test. From field activity, three adult mosquitoes species were found i.e. Anopheles vagus, An. annularis and An. maculatus. Nulliparous and parous mosquitoes from adult mosquito based on the examination of their tracheole skeins of ovarium were found from the collected mosquitoes although oocyst in midgut and sporozoite in salivary gland were not found during adult mosquito surgical. Similar trainings were expected to be applied in other similar areas in the future.